2014
DOI: 10.1007/s00415-014-7560-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of cerebrospinal fluid levels of oligomeric- and total-α-synuclein in premotor, motor and dementia stages of Parkinson’s disease

Abstract: High-oligomeric and low-total-α-synuclein cerebrospinal fluid (CSF) levels have been found in Parkinson's disease (PD), but with inconsistent or limited data, particularly on their clinical and structural correlates in earliest (premotor) or latest (dementia) PD stages. We determined CSF oligomeric- and total-α-synuclein in 77 subjects: 23 with idiopathic REM-sleep behaviour disorder (iRBD, a condition likely to include a remarkable proportion of subjects in the premotor stage of PD) and 41 with PD [21 non-dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 48 publications
8
83
2
7
Order By: Relevance
“…To date, inconsistent results in this respect have been related to different disease stages [11,12]. Our results suggest that SNCA polymorphisms also alter the toxicity of α-synuclein and tau even in early stages, increasing the complexity of the association between α-synuclein, tau, and neurodegeneration in PD.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…To date, inconsistent results in this respect have been related to different disease stages [11,12]. Our results suggest that SNCA polymorphisms also alter the toxicity of α-synuclein and tau even in early stages, increasing the complexity of the association between α-synuclein, tau, and neurodegeneration in PD.…”
Section: Discussionmentioning
confidence: 68%
“…Notably, both high and low CSF α-synuclein levels were related to cognitive decline, and most studies found no association between CSF tau or ptau and cognitive decline [9][10][11]. Furthermore, atrophic patterns associated with these biomarkers were also inconsistent in structural neuroimaging studies [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between CSF α -synuclein levels and longitudinal atrophy has been relatively understudied (Campbell et al., 2015, Compta et al., 2014, Mattsson et al., 2013). In our present study, CSF α -synuclein was not associated with whole-brain atrophy or with ventricular enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, CSF α -synuclein was not associated with whole-brain atrophy or with ventricular enlargement. This runs counter to previous studies, where reductions in CSF α -synuclein have been shown to correlate with functional deficits in motor networks (Campbell et al., 2015) and frontal atrophy in nondemented PD (Compta et al., 2014). Interestingly, Compta et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation